The Effect of Diabetic Foot Exercises on Sensitivity and Deformities (Motor) of the Feet in Patients with Type 2 Diabetes Mellitus with Neuropathy Complications - Azali, Lalu M. Panji; Salsabila, Adinda Novia; Suryandari, Dewi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Neuropathy is a common chronic complication in people with diabetes. Neuropathy refers to diseases that affect various types of nerves, including sensory, motor, and autonomic nerves. Diminished foot sensitivity and structural abnormalities may impede the patient's ability to perceive foot injuries, increasing the risk of more serious complications. Foot exercise is an effective method for people with diabetes mellitus to prevent injury and improve blood circulation in the feet. It improves blood circulation, strengthens the small muscles of the foot, and prevents foot deformities. This study aimed to determine the effect of diabetic foot exercises on foot sensitivity and motor deformity in type 2 diabetes mellitus patients with neuropathy. Method:This study employed a quantitative method with a one-group pre-test and post-test design. The sampling technique used purposive sampling with 35 respondents based on the inclusion and exclusion criteria. The data were collected through interviews and assessment of sensitivity and foot deformity. Sensitivity was measured using a 10-gram Monofilament Test, while foot deformities were evaluated with a deformity observation sheet. The statistical analysis test revealed that right foot sensitivity obtained a p-value = 0.001 (<0.05) and left foot sensitivity had a p-value = 0.013 (<0.05). The foot deformity signified p-value = 1.000 (>0.05). Diabetic foot exercise has a significant effect on foot sensitivity. However, it did not reveal a significant impact on motor foot deformity in type 2 diabetes mellitus patients with neuropathy complications in the Working Area of Puskesmas Gambirsari Surakarta.